Feudal Society - Bloch, Marc (London, 1962)
Feudal Society is great work of historical synthesis in the finest French tradition. The author treats feudalism as a living and vitalising force in the society of Western Europe from the ninth to the thirteenth century. After surveying the social and intellectual conditions in which feudalism developed, Bloch examines the nature of the bond of kinship both as a predecessor and as a concomitant of vassalage. The core of the book is a masterly account of the creation of ties of dependence and of relations of lord and vassal, and the origins and nature of the fief. The nobility and their way of life, knighthood and chivalry, the clergy and other forces in society are also portrayed, and the work concludes with a discussion on feudalism as a type of society. Throughout the author treats history as a living organism and endless process of creative evolution.
Keywords: Feudalism